Business Model Innovation Based on Sustainability: Synthesizing Strategies of Smes and Social Organization - Agniya Thahira; Vuan Maharani; Siti Mukamimah; Ana Rimbasari; Afriansyah Tanjung (www.amertainstitute.com, 2025)
This study aims to explore how the strategic goals of small and medium-sized enterprises (SMEs) and social organizations influence the pathways of business model innovation (BMI) and the implementation of sustainability. It integrates the BMI pathway perspective from SMEs with the Sustainable Business Model Canvas approach to understand how organizations balance business growth with social and environmental impact. The research employs a multiple case study method involving 10 organizations (consisting of SMEs and social enterprises) that are either in the process of or have already undertaken business model innovation. Data were collected through in-depth interviews and secondary documentation, then analyzed using a combination of the Business Model Canvas and the Sustainable Business Model Canvas approaches, along with the Activity System Framework. The study finds that the strategic objectives of organizations—both economic and socio-environmental—shape distinct pathways for business model innovation. SMEs tend to initiate innovation from the standpoint of profitability or growth, whereas social organizations focus more on integrating social and environmental values. This is an exploratory study and is limited to a small number of organizations. Further research using a quantitative approach is needed to generalize the findings. Nevertheless, the results enrich our understanding of how business model innovation can be aligned with strategic goals and sustainability, especially in contexts with limited resources. This study provides practical guidance for SME and social organization practitioners to manage their innovation pathways more deliberately by considering the balance between economic, social, and environmental values. The business model and sustainability canvases have proven to be effective tools for helping organizations design impactful innovation strategies. The research introduces an integration between the SME BMI pathway approach and the Sustainable Business Model Canvas, which has been rarely addressed in previous literature. By combining these two approaches, the study offers a new framework for understanding the business model innovation process across different types of organizations that pursue sustainability in a strategic manner. Keywords: Business Model Innovation; Business Model Canvas; Sustainability; SMEs (Small and Medium-sized Enterprises); Social Organizations.